Spatial Distribution of Drug-Resistant Tuberculosisin Makassar City, South Sulawesi Province, Indonesia - Zainuddin, Andi Alfian; Soma, Andang Suryana; Kasim, Muhammad Firdaus; Ramadany, Sri; Djaharuddin, Irawati (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
This study aims to determine the domicile distribution, find out the high-risk areas, and determine the risk of drug-resistant tuberculosis patients based on patient location in 15 districts of Makassar City from Tuberculosis register data of South Sulawesi Provincial Health Office in December 2017 – April 2019 period. Gen Xpert rapid or drug sensitivity examinations were used to define drug-resistant tuberculosis. The domicile location of patients was geocoded by maps in Google Earth and aggregated per area by using Kernel Density analysis using ArcView GIS 10.3 software. We found that drug-resistant tuberculosis cases tended to be clustered in the western part of Makassar City, an area with a fairly high population density. There were areas with the highest concentration of predicted cases as a high risk of transmission of drug-resistant TB, around the Bontoala District, Makassar District, and Mamajang District. Healthcare facilities located in hot spots area need to be equipped with molecular rapid test facilities and conduct drug sensitivity tests for all suspected tuberculosis patients. Further research needs to be carried out to determine the distribution of tuberculosis patients who are sensitive and resistant to drugs.